Management of Parotid Metastatic Cutaneous Squamous Cell Carcinoma: Regional Recurrence Rates and Survival. (August 2018) - Hirshoren, Nir; Ruskin, Olivia; McDowell, Lachlan J.; Magarey, Matthew; Kleid, Stephen; Dixon, Benjamin J.
Objectives: Extent of parotidectomy and neck dissection for metastatic cutaneous squamous cell carcinoma (cSCC) to the parotid is debated. We describe our experience, analyzing outcomes (overall survival and regional recurrence) associated with surgical extent and adjuvant treatment. Study Design: A retrospective cohort study of parotidectomy with or without neck dissection for metastatic cSCC. Setting: A tertiary referral cancer center in Australia. Subjects and Methods: The study group consisted of patients with metastatic cSCC involving the parotid gland who underwent a curative-intent parotidectomy (superficial or total), with or without neck dissection, between 2003 and 2014. Demographic and clinical data, treatment modalities, and outcome parameters were collected from the electronic institutional database. Results: Of 78 patients, 65 underwent superficial parotidectomy. Median follow-up was 6.5 years. Sixty-four patients (82%) patients received adjuvant radiotherapy. Cervical lymph nodes were involved in 6 (24%) elective neck dissections. Involved preauricular, facial, external jugular, and occipital nodes occurred in 36.9%. Adjuvant radiotherapy was associated with improved 5-year survival—50% (95% CI, 36%-69%) versus 20% (95% CI, 6%-70%)—and improved 2-year regional control: 89% (95% CI, 67%-100%) versus 40% (95% CI, 14%-100%). The ipsilateral parotid bed recurrence rate was 3.7% for those who received adjuvant radiotherapy and 27% for those who did not receive radiotherapy. Conclusion: This study supports surgery plus adjuvant radiotherapy as a standard of care for metastatic cSCC. The low incidence of parotid bed recurrence with this approach suggests that routine elective deep lobe resection may not be required.